2020
DOI: 10.1515/noise-2020-0022
|View full text |Cite
|
Sign up to set email alerts
|

Hitting the ‘pause’ button: What does COVID-19 tell us about the future of heritage sounds?

Abstract: Human existence is accompanied by environmental sounds as by-products of people’s activities and sounds that are intentionally generated to allow human society to function. The resulting soundscapes that surround people’s daily existence are subject to technological, as well as behavioural change. Cultural heritage management has begun to address the question of which sounds and soundscapes should be preserved and maintained as part of humanity’s legacy to future generations. A side-effect of the dramatic soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 88 publications
1
23
0
Order By: Relevance
“…Measurement stations around France detected a 4-6 dB reduction in traffic noise, which is about a 60-75% energy reduction, and was consistent with government reports on the scale of reduction in traffic volumes also having been reduced in this 60-75% range [11]. In terms of pedestrians, Melbourne, Australia released data showing that pedestrian use was only 14.6% of 2019 pre-pandemic levels in its Central Business District [12]. One important facet to note about the reductions in overall traffic volumes however is that average vehicle speeds actually increased in many areas due to the roads being more open.…”
Section: Reduction In Traffic Noisesupporting
confidence: 79%
See 1 more Smart Citation
“…Measurement stations around France detected a 4-6 dB reduction in traffic noise, which is about a 60-75% energy reduction, and was consistent with government reports on the scale of reduction in traffic volumes also having been reduced in this 60-75% range [11]. In terms of pedestrians, Melbourne, Australia released data showing that pedestrian use was only 14.6% of 2019 pre-pandemic levels in its Central Business District [12]. One important facet to note about the reductions in overall traffic volumes however is that average vehicle speeds actually increased in many areas due to the roads being more open.…”
Section: Reduction In Traffic Noisesupporting
confidence: 79%
“…Previous studies pointed out this emergence of previously less audible sounds in the absence of typical city noises, such as birds [11] and Rome's famous Trevi fountain being more distinguishable and more audible further away than in previous years [23]. Conversely, this new audibility increased noise complaints in New York City from emergency sirens [12]. While annoyance complaints about single sources may have risen, a study from Dallas, USA found an overall 14% drop in noise complaints, with those complaints from the city center explaining the majority of that drop [24].…”
Section: Festival Sounds and The Covid-19 Sound Environment As-experiencedmentioning
confidence: 96%
“…In particular, respondents reported hearing less traffic noise and more nature sounds. Elsewhere, hand-clapping events took place during the coronavirus pandemic, and out-of-order church bell ringing has been observed, e.g., in Australia, which provided unique elements to the soundscape [ 11 , 12 ]; however, no special public sound events were performed by the citizens of Bochum.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent press release by the Charles Darwin Foundation (CDF, 2020), Galapagos penguins (Spheniscus mendiculus) and flightless cormorant (Phalacrocorax harrisi) which have been tracked for the last 30 years are showing increased numbers of individuals, 1,940 and 2,290 respectively, which is a record for these species. The most plausible reason for this is the decrease in noise during pandemic restrictions (Spennemann and Parker, 2020), as it has been shown to affect the behavior of dolphins, sea turtles, sea birds, and other species (Samuel et al, 2005;Hazel et al, 2007;Ketten, 2008), also the event la Niña event 2020-2021 is playing role on this growing number (Lerma et al, 2020). Nonetheless, specific research must be conducted to investigate these possible reasons.…”
Section: Discussionmentioning
confidence: 99%